Exploring employee retention strategies in Indonesian startups: A qualitative study of human resource management practices - Mulyadi, Mulyadi; Sumardin, Sumardin; Sari, Dewi Permata; Sabri, Sabri; Sudianto, Sudianto (Annals of Human Resource Management Research, 2025)
Purpose: Startups in Indonesia have experienced rapid growth over the past decade but face significant challenges in retaining talent due to organizational dynamics and evolving employee expectations. This study explores employee retention strategies implemented by Indonesian startups by examining current human resource management practices. Methodology: A qualitative approach was employed, using semi-structured interviews with HR leaders and decision-makers from ten high-growth startups in Jakarta, Bandung, and Surabaya. Results: The study identified key retention strategies including meaning-driven work culture, flexible work arrangements, equity-based compensation, and individualized career pathways. Startups that aligned HR initiatives with intrinsic motivation and employee well-being reported higher retention rates. Founder-led engagement, agile feedback loops, and cross-functional mobility were also notable as innovative HR practices in the startup context. Conclusions: Retention in Indonesian startups is significantly enhanced through HR strategies that prioritize intrinsic motivators and employee well-being, particularly in competitive talent environments. Limitations: The study’s qualitative nature and geographic focus on three cities may limit broader generalization across Indonesia's diverse startup ecosystem. Contribution: This study offers practical insights into effective HR strategies for talent retention in emerging market startups, emphasizing founder involvement and adaptive HR innovations.